2011
DOI: 10.1089/ten.teb.2010.0552
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation of Electrosprayed Fibers for Tissue Regeneration

Abstract: Electrospinning is a widely established polymer-processing technology that allows generation of fibers (in nanometer to micrometer size) that can be collected to form nonwoven structures. By choosing suitable process parameters and appropriate solvent systems, fiber size can be controlled. Since the technology allows the possibility of tailoring the mechanical properties and biological properties, there has been a significant effort to adapt the technology in tissue regeneration and drug delivery. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 198 publications
(185 reference statements)
0
45
0
Order By: Relevance
“…However, methods to control the thickness of highly porous electrospun scaffolds are limited because electrospun fibers with a large pore size 8,24 and controlled scaffold thickness cannot be simultaneously collected with traditional flat collectors. 28 In this study, we simultaneously engineered the thickness and the pore size of electrospun fibers by designing a novel collector configuration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, methods to control the thickness of highly porous electrospun scaffolds are limited because electrospun fibers with a large pore size 8,24 and controlled scaffold thickness cannot be simultaneously collected with traditional flat collectors. 28 In this study, we simultaneously engineered the thickness and the pore size of electrospun fibers by designing a novel collector configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Although the diameter of the highly porous region in this study was 0.5 cm, this region could be expanded by enlarging the diameter of the hole to as large as approximately 10 cm. 8 scaffold characterization scanning electron microscopy imaging Fabricated 2D and 3D scaffolds were analyzed using a SUPRA25 electron microscope (Carl Zeiss, Jena, Germany) at an acceleration voltage of 10 kV. Samples were attached to a silicon wafer by using carbon tape (3M, St Paul, MN, USA) and sputter-coated with gold for 1 minute prior to scanning electron microscopy (SEM) analysis.…”
Section: Fabrication Of Highly Porous Electrospun Scaffold With Tunabmentioning
confidence: 99%
See 1 more Smart Citation
“…Morton, in 1914 J. Neleny reported that a liquid jet could be emitted from a charged liquid droplet in the presence of an electrical field [1]. Twenty years later, when A. Formhals patented a process that allowed the spinning of synthetic fibres using electric charges [2,3], electrospinning became a valid technique to produce small-sized fibres. Following Formhals' pioneering work, researchers have focused on an in-depth understanding of the electrospinning process.…”
Section: Overview Of the Electrospinning Processmentioning
confidence: 99%
“…On the other hand, 3-D scaffolds fabricated on the nanoscale exhibit more success in directing cells towards certain cellular morphologies, differentiation, and many other important cellular functions, but usually at the cost of reduced mechanical strength. 17 Therefore, in order to establish in vivo microenvironments, the next generation of 3-D tissue-engineering scaffolds should integrate both microstructures and nanoscale architectures, which could enhance both mechanical strength and cellular functions. However, there are some difficulties in fabricating thick 3-D microstructures, scaffolds with a nanoscale integration or morphology due to the characteristics of polymers.…”
Section: Introductionmentioning
confidence: 99%